Effect of SeO2 on corrosion resistance of micro-arc oxidation - Zhang, D.F.; Zheng, R.; Chen, X.W.; Zhang, G.H. (Surface engineering, 2023)
In order to make titanium alloy implants have better corrosion resistance in the human body, selenium-containing coating was added to the surface of Ti6Al7Nb through micro-arc oxidation. The results indicate that the coating has a higher thickness and lower roughness after the addition of selenium element. XRD, SEM, and XPS analysis showed that selenium element was successfully added into the coating. Then the dynamic polarization curve and EIS indicate that the prepared samples have better corrosion resistance in SBF solution compared to the unadded samples, (i corr ) and (E corr ) are 2.695 × 10−8 A·cm−2 and 0.101 V, respectively. The addition of selenium helps to improve the biological corrosion resistance of the sample in body fluids.